Thyroid abnormality in patients with psoriasis: prevalence and association with severity - Luiza de Castro Fernandes; Ana Carolina Belini Bazan Arruda; Lisa Gava Baeninger; Debora Pedroso Almeida; Danilo Villagelin (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background: Psoriasis is associated with several comorbidities and its association with thyroid abnormality has been hypothesized. Objective: To assess the prevalence of thyroid abnormality in Brazilian patients with psoriasis and to analyze its association with severity, presence of psoriatic arthritis and immunobiological treatment. Additionally, to compare results with literature as a control. Methods: In this observational study, clinical and laboratory data of patients followed from January 2018 to December 2019 were analyzed. Thyroid abnormality was assessed through the current history of thyroid disease and laboratory tests - thyrotropin (TSH), free thyroxine (FT4), antithyroid peroxidase (anti-TPO) and antithyroglobulin (anti-TG) antibodies. Patients were classified according to psoriasis severity - Psoriasis Area and Severity Index (PASI), presence of psoriatic arthritis, and current treatment. Subsequently, the results were compared with a control group selected from the literature review. Results: Of the 250 included patients, 161 were eligible. The prevalence of thyroid abnormality was 28.57% and of hypothyroidism, 14.91%. The mean age was 55 years and the median PASI was 2.2. There was no association between thyroid abnormality and PASI (p = 0.8), presence of psoriatic arthritis (p = 0.87), or use of immunobiological therapy (p = 0.13). The literature control group included 6,227 patients and there was a statistically significant difference for the hypothyroidism variable (p < 0.0001).